THE EFFECT OF PERCEPTIONS UMKM OWNERS, ACCOUNTING KNOWLEDGE, LEVEL OF EDUCATION AND BUSINESS SCALE ON THE USE OF ACCOUNTING INFORMATION SYSTEMS IN UMKM KAMPUNG TOPI PUNGGUL - Rohmah , Nur; Rahmawati, Imelda Dian (Journal of Social Science, 2024)
This study aims to determine the effect of the variable perceptions UMKM owners, accounting knowledge, education level and business scale on the use of accounting information systems in UMKM Kampung Topi Punggul. The population of this research is business actors UMKM in Kampung Topi Punggul. Sampling used a purposive sampling technique, taking samples with certain criteria where there were 47 respondents who fit the criteria of craftsmen of hats, ties and socks. The data analysis technique used in this study is multiple linear regression using the SPSS version 26 test tool. The results of this study found that the variables of accounting knowledge and business scale proved to have an effect on the use of accounting information systems. Meanwhile, the variable perceptions of UMKM owners and education levels have no effect on the use of accounting information systems. It is hoped that this research will be able to provide consideration for UMKM actors in Kampung Topi Punggul that with good accounting they can be used to manage their business activities and make decisions in the future